2020
DOI: 10.1016/j.jclinane.2020.110033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of five critical COVID-19 patients treated with extracorporeal membrane oxygenation in Leishenshan Hospital in Wuhan

Abstract: Highlights Providing early ECMO support due to carbon dioxide retention and on-time decannulation may be more beneficial to patients. The duration from tracheal intubation to ECMO cannulation was more than 7 days in some patients. The application rules of ECMO vary in different regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Patients with ARDS and requirement for respiratory support need urgently to be transferred to the intensive care unit (ICU). It is reported that nasal cannula or mask, high-flow nasal cannula, non-invasive ventilation (NIV), invasive mechanical ventilation (IMV), and veno-venous extracorporeal membrane oxygenation (VV-ECMO) were widely used in COVID-19 according to the severity of respiratory dysfunction (2)(3)(4). Cardiac injury is common in COVID-19, with an incidence of 36% and closely related to a higher risk of mortality (5).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ARDS and requirement for respiratory support need urgently to be transferred to the intensive care unit (ICU). It is reported that nasal cannula or mask, high-flow nasal cannula, non-invasive ventilation (NIV), invasive mechanical ventilation (IMV), and veno-venous extracorporeal membrane oxygenation (VV-ECMO) were widely used in COVID-19 according to the severity of respiratory dysfunction (2)(3)(4). Cardiac injury is common in COVID-19, with an incidence of 36% and closely related to a higher risk of mortality (5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the data source was considered unreliable. As a possible population overlap was identified in 22 articles 13,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (Table S1), only the most recent or complete studies reporting the larger cohorts of patients were included. 13,33,34,[36][37][38][39][40]48 As one of the included study reports data from the ELSO registry accounting for 213 contributing centers worldwide (Figure 2), it was not possible to exclude with certainty the presence of a partial overlap with other selected studies published by centers contributing to the ELSO registry.…”
Section: Literature Searchmentioning
confidence: 99%